2023
DOI: 10.3390/ijms241512506
|View full text |Cite
|
Sign up to set email alerts
|

A Multifunctional Polyethylene Glycol/Triethoxysilane-Modified Polyurethane Foam Dressing with High Absorbency and Antiadhesion Properties Promotes Diabetic Wound Healing

Chiu-Fang Chen,
Szu-Hsien Chen,
Rong-Fu Chen
et al.

Abstract: The delayed healing of chronic wounds, such as diabetic foot ulcers (DFUs), is a clinical problem. Few dressings can promote wound healing by satisfying the demands of chronic wound exudate management and tissue granulation. Therefore, the aim of this study was to prepare a high-absorption polyurethane (PU) foam dressing modified by polyethylene glycol (PEG) and triethoxysilane (APTES) to promote wound healing. PEG-modified (PUE) and PEG/APTES-modified (PUESi) dressings were prepared by self-foaming reactions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(36 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Polyethylene glycol [74,75] Self-foaming reactions. Nondiabetic and diabetes mellitus rat wound models.…”
Section: Process and Methods Research Models Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyethylene glycol [74,75] Self-foaming reactions. Nondiabetic and diabetes mellitus rat wound models.…”
Section: Process and Methods Research Models Characterizationmentioning
confidence: 99%
“…Polyethylene glycol polymer, because of its good water solubility and good compatibility with many organic components, has been widely used. Chen et al prepared a PEG and triethoxysilane (APTES) modified high absorption polyurethane foam dressing (PUESi) [74]. The research results indicated that PUESi dressings not only had good adhesive resistance and deformation absorption ability, but also could effectively promote wound healing.…”
Section: Polyethylene Glycol (Peg)mentioning
confidence: 99%
“…3 In the 13.7 million infection-related deaths estimated to occur in 2019, deaths associated with bacterial infections accounted for 13.6% of all deaths globally, with the highest number of deaths associated with Staphylococcus aureus at 1.1 million deaths globally and 950,000 deaths with E. coli. 6 The overuse of antibiotics has led to a gradual increase in bacterial resistance to antibiotics, and to promote the healing of such chronic wounds over the past decades, there are a number of materials currently available on the market reported to be used for the treatment of chronic wounds such as gauze, polyurethane foams, hydrocolloids and hydrogels, calcium/ sodium alginate, and so forth. 4 Among them, polyurethane foams have almost no cytotoxicity, moderate water vapor permeability, good biocompatibility, and mechanical properties and are widely used in the treatment of chronic wounds.…”
Section: Introductionmentioning
confidence: 99%
“…However, the antimicrobial activity of conventional polyurethane foam dressings prepared from nonrenewable resource petroleum is relatively low. The polyether or polyester chain segments in PUF materials can be a carbon source for microbial growth . Therefore, polyurethanes as dressings are susceptible to bacterial interference in treating wounds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation